Comparative Study Between Learning English Using Video And Textbook In Speaking Skill At A Grade Xi Smk Mitra Nusantara Jati Bening Baru, Pondok Gede Bekasi - Novelia, Novelia; Siahaan, Leroy Holman; Subadar, Subadar (Universitas Pahlawan Tuanku Tambusai, 2024)
The ability to speak English is an essential skill that students must have to prepare for the future and communicate effectively in an increasingly connected world. In Indonesia, a developing country with linguistic diversity, mastery of English is a key skill to access opportunities in education, careers and international life. However, the development of speaking skills is often a challenge in formal educational settings such as schools. This study aims to compare the effectiveness of two English learning methods, namely the use of videos and textbooks, in developing the speaking skills of grade XI students of SMK Mitra Nusantara Jati Bening Baru, Pondok Gede, Bekasi.The research method used is comparative quantitative research with descriptive and inferential statistical analysis. The results of the Independent Samples T-Test showed that there was no significant difference in students' speaking skills between the group taught using videos and the group taught using textbooks, with a Sig. (2-tailed) of 0.113 indicating that the mean difference of 2.920 between the two groups was not significant at the 0.05 level of significance. This finding indicates that both teaching methods are equally effective in improving students' speaking skills.This study is expected to provide valuable insights for teachers and school staff regarding the use of videos and textbooks in English language teaching, as well as assist in developing more innovative curriculum and teaching methods according to the needs of students in the digital era.